A simple and effective design method for multiband filtering power divider. Issue 7 (7th March 2020) - Tang, Liming; Zhang, Gang; Guan, Xuehui; Yang, Jiquan
Abstract: This letter presents a simple and effective design method for multiband filtering power divider (FPD) in wireless communication systems. By elaborately coupling multiple pairs of stub‐loaded resonators (SLRs) with input/output feedlines, a flexible topology for multiband FPD is built. Not only can each pair of the SLRs generate one passband, but also control the respective center frequency and bandwidth independently. Meanwhile, isolation resistors are arranged between each pair of the SLRs to independently adjust each band isolation, finally achieving nice isolation over a wide frequency band. To validate the design concept, a prototype triple‐band FPD working at 1.30, 1.62, and 2.22 GHz is devised, simulated, and tested. Measurements have good agreement with simulations, indicating that the FPD has the advantages of its independently controllable frequency and bandwidth, high passband selectivity, and good isolation over a broadband frequency band.